Theory and test of underground explosions: Coupling rule between cratering and ground shock - Wei Guo; Jie Li; Benjun Shi; Tianhan Xu; Xiaohui Xu; Gan Li; Jie Shi (Underground Space, 2024)
Calculating the parameters of the ground shock induced by an underground explosion is a complex energy coupling problem. It is difficult to establish a unified ground shock coupling law from limited test data. This paper summarizes the research results obtained at home and abroad and systematically analyzes the coupling mechanism of craters formed by an underground explosion and the ground shock. The differences between the concepts of “closed-explosion critical depth” and “equivalent closed-explosion critical depth” are clearly explained. The spreading of the ground shock energy is attributed to the explosive expansion of the air cavity, revealing a linear relationship between the volume of the cavity region (or the volume of the crack region) and the ground shock energy associated with the underground explosion. The proportionality factor is related to the mechanical properties of the medium and is independent of the magnitude of the explosion equivalent. Based on this, a theoretical calculation formula and conversion method for the ground shock coupling coefficient were established. Explosion tests were conducted in clay and Plexiglass under varying burial depths. The test results were consistent with the theoretically calculated results. Our study provides a theoretical basis for the design of explosion-resistant structures in underground engineering.